Orchids of the Southern Cone (1830–2000) – Part IV. Maevia Noemí Correa’s Flora Patagonica - Ossenbach, Carlos (2023)
Maevia Noemí Correa (1914–2005) will always be remembered as the director and editor of an outstanding work, Flora Patagonica, in which she assumed the treatment of several plant families, among them the Orchidaceae. Published between 1969 and 1999, the work was the product of 30 years of dedicated research and fieldwork, resulting in the publication of eight volumes and extraordinary plant collections, now housed in Argentinian and foreign herbaria. Popularly known as The Dame of the Orchids, Correa must be considered one of the most relevant Argentinian botanists of the 20th century. In honor of her birth on February 14th, the day has been designated as "The Day of the Orchidophile”.